A Review on the Impact of Fallback Factor on Intermittent Gas and Gas-Assisted Plunger Lifts - Erasmus Mensah; Smith Leggett (Geosciences, 2025)
In intermittent gas lift (IGL), not all the liquid initially in the tubing is usually produced at the surface in one cycle. This is due to a concept known as fallback, which occurs when some amount of the initial liquid column drops back to join the next slug. We conducted a review of earlier works on IGL and the behavior of the fallback factor. The dependence on the fallback factor on the operational conditions such as slug velocity, valve opening pressure, valve closing pressure, casing–tubing pressure ratio, diameter of tubing, and amount of gas injected during IGL are discussed in this paper. The effect on the shape and stability of the nose of the Taylor bubble on the lifting efficiency of the bubble is also explained. In trying to reduce the fallback factor per cycle, there have been recommendations to combine gas lift with plunger lift. We also present the results of this combination and the effects on the fallback factor in gas-assisted plunger lift (GAPL). More light is shed on the behavior of the velocity of the liquid slug and how it affects the fallback factor during IGL. The behavior of the fallback factor with an increase or decrease in plunger velocity during GAPL is also presented in this paper. This review is categorized into experimental and numerical studies on fallback factor to evaluate their impact on production efficiency in IGL and GAPL. Additionally, different formulas for fallback proposed by different literature are compiled.